2008
DOI: 10.1089/ast.2006.0092
|View full text |Cite
|
Sign up to set email alerts
|

A Facility for Long-Term Mars Simulation Experiments: The Mars Environmental Simulation Chamber (MESCH)

Abstract: We describe the design, construction, and pilot operation of a Mars simulation facility comprised of a cryogenic environmental chamber, an atmospheric gas analyzer, and a xenon/mercury discharge source for UV generation. The Mars Environmental Simulation Chamber (MESCH) consists of a double-walled cylindrical chamber. The double wall provides a cooling mantle through which liquid N(2) can be circulated. A load-lock system that consists of a small pressure-exchange chamber, which can be evacuated, allows for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 48 publications
0
24
0
1
Order By: Relevance
“…For microbiological studies the cores were split into 5-cm-long segments, placed into sterile plastic bags, stored frozen in the field within a hole excavated in the permafrost, transported frozen to the Soil Cryology Laboratory in Pushchino, Russia, and then transported frozen by air to Kennedy Space Center, FL. The samples represent epigenetically frozen layers of Holocene age (6)(7)(8) formed by refreezing of sediments that had melted and drained. They are hydrocarbonate-calcium fine-grained peaty sandy-loams, firmly bound by ice (ice content 25-37%), with pH close to neutral (6.8-7.2) and containing organic carbon (0.5-2.0%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For microbiological studies the cores were split into 5-cm-long segments, placed into sterile plastic bags, stored frozen in the field within a hole excavated in the permafrost, transported frozen to the Soil Cryology Laboratory in Pushchino, Russia, and then transported frozen by air to Kennedy Space Center, FL. The samples represent epigenetically frozen layers of Holocene age (6)(7)(8) formed by refreezing of sediments that had melted and drained. They are hydrocarbonate-calcium fine-grained peaty sandy-loams, firmly bound by ice (ice content 25-37%), with pH close to neutral (6.8-7.2) and containing organic carbon (0.5-2.0%).…”
Section: Methodsmentioning
confidence: 99%
“…The current surface environment of Mars presents formidable challenges to life, such as a scarcity of liquid water and organic nutrients, extreme low temperatures, a low-pressure CO 2 -dominated atmosphere, harsh solar and galactic cosmic radiation, and a lack of organic nutrients (5). To address the question of whether terrestrial life could survive and grow in the martian environment, several researchers have turned to Mars environmental simulations conducted in chambers that replicate the temperature, pressure, atmospheric composition, regolith composition, and solar radiation environment of the Mars surface and near subsurface (6). Results from past experiments testing the ability of dozens of terrestrial microorganisms to grow in one such simulator demonstrated that the combination of low pressure (P; 7 mbar), low temperature (T; 0°C), and anoxic atmosphere (A), called here low-PTA conditions, posed significant barriers to growth (5,7,8).…”
Section: Astrobiology | Planetary Protectionmentioning
confidence: 99%
“…For this reason, Mars environmental simulation experiments have been conducted to estimate (i) the survival rates of terrestrial microorganisms and (ii) the persistence of organic molecules on Mars (3,4,10,15,25,29,30,37,38,45). Historically, several studies have explored the resistance of bacterial spores to simulated Martian conditions (8,10,12,14, and references therein); these studies have concentrated mainly on the survival of spores of wild-type strains of various spore-forming species (10,32,(38)(39)(40). More recent experiments have attempted to better understand the molecular factors causing spore resistance to environmental extremes, in which mainly spores of the model organism Bacillus subtilis that carry mutations affecting spore protective factors or spore DNA repair systems have been used (9, 18-23; reviewed in references 16, 28, 41, and 42).…”
mentioning
confidence: 99%
“…Strain SPM-9 T produced a yellow diffusible pigment while strain SPM-10 T produced a dark orange non-diffusible pigment. A third isolate, M5-H2, was recovered from the same permafrost soil sample after the sample had been exposed to simulated Martian conditions in a Mars simulation chamber (Jensen et al, 2008). Strain M5-H2 produced a deep orange non-diffusible pigment and appeared to be closely related to isolate SPM-10 T .…”
mentioning
confidence: 99%